ENGLISH PHONEMIC AWARENESS OF INDONESIAN EFL LEARNER - Lintar Yurianto; Alies Poetri Lintangsari; Widya Caterine Perdhani (Erudio Journal of Educational Innovation, 2021)
Phonemic awareness (PA) is the ability to hear and manipulate the sounds in spoken words and the understanding that spoken words and syllables are made up of sequences of speech sounds. PA is important because it can help students to understand the alphabetic principle and it requires students to notice how letters represent sound. This research conducted to find out the phonemic awareness of Indonesian EFL learners. Involving 100 third-semester students of English Language Education Program Universitas Brawijaya, this research examines the English Phonemic Awareness of the Indonesian EFL learners. The instrument of this research is Phonemic Awareness Test adopted from Heggerty (2017). The test measured 5 skills: the awareness of (1) onset fluency, (2) final sound, (3) medial sound, (4) phoneme blending, and (5) phoneme segmenting. The findings of this research reveal that the Phonemic Awareness of Indonesian EFL learners are categorized poor with mean 17.9 (Advance > 29.7). They are struggling in identifying onset fluency, it categorized poor with mean 2.85. Followed by identifying final sound with mean 3.87 from 10 and identifying medial sound with mean 3.97 from 10 that are categorized medium. In blending skill, the mean score is categorized medium since the mean 5.09 from 10. The last is segmentation skill who have category poor since the total score is 1.47 from 10. It can be concluded that Indonesian EFL learners are struggling in identifying English phoneme.